Dinámica de los operadores de un campo escalar complejo bidimensional en la representación de Heisenberg - Villegas Silva, Fulgencio (2014)
We show the motion equations of the field operator and canonical momentum that describe the complex two-dimensional scalar field, using for it’s representation the Heisenberg formalism. This analysis is based on the complex two-dimensional scalar field Lagrangian which is invariant under the SU(2) global symmetry where the transformation matrix is expanded in function of the Pauli matrices and is parameterized as a function by the Euler angles.